Preparation and Characterization of Silica/SolutionStyrene-Butadiene Rubber Composite UsingAlkenylalkoxysilane - Kim, Dae Jin; Jung, Dong Eui; Yoo, Bok Ryul (John Wiley & Sons Inc., 2026)
In this study, silica/solution styrene-butadiene rubber (SSBR) composites (C-allyl, C-vinyl, and C-octenyl) were prepared using various alkenyltrimethoxysilane [alkenyl(TMS)]-based coupling agents (alkenyl = allyl-, vinyl-, and 7-octenyl) and their physical and viscoelastic properties were compared to those of composites prepared employing tetrasulfide silane, TESPT, referred to as C-TESPT. The results revealed that the C-allyl exhibited superior properties, primarily due to enhanced silica dispersion and increased crosslink density. Bound rubber analysis confirmed that the reduced hydrophobicity of alkenyl(TMS), particularly in the C-allyl variant, enhanced silica surface modification, facilitating the formation of a more robust network. Notably, the C-allyl composites demonstrated consistent vulcanization, as evidenced by stable cure rate indices and effective thermal conductivity. Mechanical evaluations revealed that C-allyl not only exhibited improved tensile strength and wet grip performance but also better rolling resistance, attributable to its optimized filler dispersion. Furthermore, the low tan delta at 60 degrees C suggested potential enhancements in fuel efficiency, particularly relevant to the tire industry. These findings underscored the potential of alkenyl(TMS)-based coupling agents, especially in C-allyl configurations, as sustainable and high-performance alternatives to TESPT in advanced tire manufacturing.